2003
DOI: 10.1001/archneur.60.5.690
|View full text |Cite
|
Sign up to set email alerts
|

Subthalamic Stimulation in Parkinson Disease

Abstract: The improvement of segmental akinesia and the observation of dyskinesias provoked by stimulation during the operation predict the best postoperative effects of bilateral STN stimulation on parkinsonian motor disability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
62
2
1

Year Published

2004
2004
2013
2013

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 91 publications
(66 citation statements)
references
References 19 publications
0
62
2
1
Order By: Relevance
“…Houeto et al [10] did not find any correlation between the postoperative clinical outcome and the extent of STN neuronal activity along the best trajectory in single-unit microrecordings. In contrast, we found that the clinical outcome correlated with the length of neuronal hyperactivity in multi-unit recordings.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Houeto et al [10] did not find any correlation between the postoperative clinical outcome and the extent of STN neuronal activity along the best trajectory in single-unit microrecordings. In contrast, we found that the clinical outcome correlated with the length of neuronal hyperactivity in multi-unit recordings.…”
Section: Discussionmentioning
confidence: 99%
“…In the literature, pre-operative predictive factors for STN-DBS outcome include young age and high baseline values or levodopa responsiveness of UPDRS III scores, in particular regarding the axial subscore [8,9,10,11,12,13,14]. Herein, patients have been selected to the bilateral STN stimulation procedure according to a specific set of clinical characteristics.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations